Implantación de un sistema contable y aplicación de indicadores financieros en el almacén y mueblería “Cosas de Casa” de la ciudad de Cariamanga cantón Calvas, provincia de Loja, periodo enero–marzo del 2015 - Quezada Bustos, Martha Cecilia (2015)
The IMPLEMENTATION OF AN ACCOUNTING SYSTEM AND APPLICATION OF FINANTIAL INDICATORS IN THE WAREHOUSE AND MUEBLERIA “COSAS DE CASA” IN CARIAMANGA CITY CANTON CALVAS, LOJA PROVINCE, PERIOD JANUARY-MARCH 2015 has been realized with the proposal of giving an adequate and efficient Accounting System in benefit of its owner Mr. Celso Iván Álvarez Saavedra, based on the Academic Regime Regulation of the national University of Loja, previous to obtain the degree of Engineer in Accounting and Auditing CPA. The aimed goals were achieved, with the elaboration of a accounts Manual and Plan, it was classified and determined the initial inventory, the file and the correct register of the counting information in chronological and sequential order gave place to the beginning of the Accounting Cycle, since the state of the initial situation until getting to the elaboration of Financial Statements, the ones that allowed the application of the Financial Indicators, always being careful with the Accounting and Taxes Norms. It is concluded that with the implementation of an accounting System and the application of the financial indicators the Warehouse and Muebleria “Cosas de Casa” has reliable, real and easy to manage information, which will allow its owner to know his financial situation when he considers it necessary and which will work as a guide for decision making. This way, he will be able to fulfill with the legal requirements of the current control organisms; reason from which it is recommended to keep this application since it will be an efficient tool to organize the business countably and also to evaluate its economic potential throughout the collected results